Preliminary dating of the Vale de Parreiras Formation of the late Famennian age, Iberian Pyrite Belt, Portugal, based on palynomorphs - Mendes, Márcia (2021)
New palynostratigraphic data were obtained from phyllites interbedded with quartzwackes of the Vale de Parreiras Formation, located to the south of the Grândola Fault in the Azinheira de Barros region, Portugal. The studied outcrops are located in the eastern bank of the Sado river. A mid-late Famennian age has been assigned based on significant presence of the key miospore species Grandispora cf. cornuta and Rugospora flexuosa, indicating a VCo Miospore Biozone for the Vale de Parreiras Formation. This age is older than previously considered for this formation, even despite the lack of palaeontological information and geochronological age determinations. This new attained palynological age provides helpful informations for the interpretation of regional tectonic structures. Also, its stratigraphic position could be reinterpreted and correlated to other late Famennian age units of Iberian Pyrite Belt, for instance, to the Phyllite-Quartzite Group. The new palynological age indicates that the Vale Parreiras Formation lithologies were deposited and belong to the same palaeogeographic realm as the former group during Late Devonian times. It may also suggest important post Variscan uplift of the Iberian Pyrite Belt in the area east of the Corona-Sado Fault and south of the Grândola Fault. These results also indicate a significant exposure of the mid-late Famennian basement wich can be considered a less favourable scenario to mineral exploration in this Iberian Pyrite Belt sector